Aconiti Lateralis Radix Praeparata ameliorates heart failure via PI3K/AKT/Bnip3 pathway - Liu, Wenxiu; Zou, Xingju; Zheng, Yang; Zhang, Yuan; Cui, Guijuan; Liu, Siyu; Sun, Chen; Peng, Cheng (Frontiers in Pharmacology, 2025)
BackgroundChronic heart failure (CHF) is one of the leading causes of high mortality worldwide. It is characterized by pathological hypertrophy and poses a major threat to human health. Aconiti Lateralis Radix Praeparata is widely used in ancient China to treat CHF. However, the pathology is obscured, necessitating further exploration.MethodsProspective targets were predicted by network analysis. A transverse aortic constriction (TAC) mice model was subsequently constructed to determine the effects of aqueous extract of Aconiti Lateralis Radix Praeparata (AEA) on CHF. The echocardiography was performed to investigate cardiac function. Histopathological analysis of cardiac tissue was conducted to assess myocardial fibrosis. Nontargeted metabolomics was performed to analyze serum metabolites. The phosphorylation level of PI3K and AKT, and downstream targets such as Bnip3, p62, Atg5, and LC3II were measured by Western blotting. In vitro, norepinephrine (NE) was used to stimulate cardiac hypertrophy. Parameters such as reactive oxygen species levels, mitochondrial membrane potential, ATP concentration, and CK/MB content were detected in H9c2 cells.ResultsAEA significantly alleviated CHF. Network analysis indicated the participation of AKT in CHF, and was modulated by Aconiti Lateralis Radix Praeparata. In vivo, AEA administration effectively ameliorated cardiac performance, evidenced by the elevation of ejection fraction. Histopathological analysis displayed a diminishment of collagen fiber. Metabolomics analysis showed that several metabolites such as tetrahydroxycorticosterone, decylubiquinone and taurocholic acid were increased in the TAC mice serum. Additionally, the phosphorylation levels of PI3K and AKT, and expression levels of Drp1, Opa1, Bnip3, p62, Atg5 and LC3II were altered in TAC group. In vitro, NE stimulation increased the cell surface area and deteriorated mitochondrial functions in H9c2 cells. However, AEA administration partially reversed such results, and the mechanism was associated with mitophagy.ConclusionThis study revealed that AEA improved cardiac function via the PI3K/AKT/Bnip3 pathway.